Hukum Islam dan Perubahan Sosial (Studi Epistemologi Hukum Islam dalam Menjawab Tantangan Zaman) - Muhammad Sulthon (Universitas Batanghari Jambi, 2019)
Deconstruction of Islamic law in accordance with the subject matter that is in harmony with the social dynamics become mainstream. This deconstruction is epistemelogi idea is applied in the form of social thought Islamic thinker Islamic law. In the Koran legislation contains general principles and legal-specific. The general principles are the true meaning and arguments behind-specific legal provisions, sometimes explicitly stated also accompany expressions of legal-specific. In the renewal of ideas Islamic law, substantive attention to texts that are definitive (absolute) and zhanni (relative). The distinction between qath'i with zhanni so stressed, because in this case it is an open space for diligence in order to respond to changing times. Deconstruction of Islamic law seeks to find knowledge that is rooted to the moderate Islamic knowledge and adaptive to the times.